2021
DOI: 10.1021/acsaem.0c03086
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed Perovskite/Perovskite Heterostructure Via a Grafting-Assisted Transfer Technique

Abstract: The outstanding properties of perovskites have attracted huge attention in optoelectronic applications. However, the current study mainly focuses on small-area single-layer perovskite films. Surface modification of the polydimethylsiloxane (PDMS) surface has the potential for successful transfer of perovskite thin films and also for forming perovskite/perovskite heterostructures. Nevertheless, current PDMS surface modification processes suffer from fast hydrophobicity gain, thus greatly inhibiting their use in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The lamination was realized with an in‐house developed hot embossing machine. [ 16d ] The machine was composed of an upper and a lower tool mounted on a fixed and a movable crossbar respectively, with an integrated heating and cooling unit, a vacuum chamber, and a drive unit. The two independently prepared layer stacks were placed on the machine plate such that the 2D and 3D perovskites face each other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lamination was realized with an in‐house developed hot embossing machine. [ 16d ] The machine was composed of an upper and a lower tool mounted on a fixed and a movable crossbar respectively, with an integrated heating and cooling unit, a vacuum chamber, and a drive unit. The two independently prepared layer stacks were placed on the machine plate such that the 2D and 3D perovskites face each other.…”
Section: Methodsmentioning
confidence: 99%
“…[ 14 ] The solution‐based deposition of quantum dot heterostructures [ 15 ] is possible, but processing a stack of planar 2D or 3D perovskite heterostructures in this way is still challenging. To solve this, lamination of two complementary half stacks is established as a method providing the flexibility of combining two separately processed perovskite layers for photovoltaic applications, [ 16 ] although here a type II band alignment to promote charge separation is targeted.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, the following methods are derived. Generally speaking, the bottom-up film patterning integration method is mainly inkjet printing, 38,96,97 while there are three top-down film patterning integration methods: (i) transfer printing; [98][99][100][101][102][103][104][105] (ii) orthogonal solvent; 40,41,[106][107][108][109][110] (iii) cross-linker post-treating. 44,45,111,112 Each of the above methods has advantages and disadvantages, which will be explained in detail below.…”
Section: Film Patterning and Integrationmentioning
confidence: 99%
“…Many experimental and theoretical studies confirmed that interface engineering is an effective approach to achieve surface passivation and further improve the stability and efficiency of PSCs. Zhang et al reported a MAPbI 3 /MAPbI 2 Br cascade structured PSC in which MAPbI 2 Br mainly acts as a hole conductor, revealing that proper arrangement of the interfacial energy band is conducive to promote charge separation in PSCs. Holmes et al have successfully fabricated three-dimensional heterojunction APbX 3 /MASnX 3 (A = FA, MA, or Cs; X = I or Br) by the sequential solution and vapor processing method, which showed an improvement in device performances.…”
Section: Introductionmentioning
confidence: 99%